Techno-economic and sensitivity analysis of coconut coir pith-biomass gasification using ASPEN PLUS. (1st March 2020) - AlNouss, Ahmed; Parthasarathy, Prakash; Shahbaz, Muhammad; Al-Ansari, Tareq; Mackey, Hamish; McKay, Gordon
Highlights: An ASPEN plus model for coconut coir pith and its char gasification was developed. Sensitivity analysis was conducted for both coconut coir pith and its char. Techno-economic analysis of coconut coir pith and its char gasification was done. Steam gasification of char can generate syngas of high yield and quality. Coconut coir pith char gasification is more economical than coir pith gasification. Abstract: The study on the steam gasification of biomass char is important to evaluate the performance of steam gasification of biomass and its char. A validated ASPEN plus model was used to investigate the effects of temperature (1023, 1073, 1123, 1173, and 1223 K) and steam-to-feed ratio (0.5, 1.0. 1.5. 2.0, and 2.5) on the syngas output and its composition using steam gasification of coir pith and its char. The study also compared the output and composition of syngas of both processes conducted at 1123 K and 0.75 (steam-to-feed ratio). The techno-economic analysis of both gasifications at the above condition was also investigated. The sensitivity analysis indicated that the temperature has both positive and negative influences; while increasing the steam-to-feed ratio has only a positive influence on the syngas output. Further, it was observed that the increase in temperature increased the yield of H2 and CO, but it decreased the yield of CO2 and CH4 . Meanwhile, it was noted that the increase in steam-to-feed ratio increased the yield of H2 and CO2 however, it decreased the yield of CO and CH4. The comparative study indicated that the coir pith char gasification generated 27% more syngas output and 25% more H2 + CO composition than the coir pith gasification. The techno-economic analysis indicated that the coir pith char steam gasification can generate 1.12 times more revenue than coir pith steam gasification. It can be concluded that the biomass char gasification is more advantageous than biomass only gasification.